Penyebab Kegagalan Negosiasi Pertanian, Jasa, dan Non-Agriculture Market Access (NAMA) dalam Doha Round Tahun 2001-2006 - Berlian, Gris Sintya (Global and Policy Journal of International Relations, 2014)
ABSTRACTDoha Round is a new round of negotiation in World Trade Organization that held on November 9-14th 2001, at Doha, Qatar. There are 21 subjects of negotiation. The deadline for reaching agreement in all subjects was in 2005 and extended in 2006. Even it was extended, the agreement still could not be reached. One reason of it was unreachable agreements in agriculture, services, and non-agriculture market access (NAMA). This article will try to examine the reason for unreachable agreements in agriculture, services, and non-agriculture market access (NAMA) based on negotiation and rational choice theory. The unreachable agreements in agriculture, services, and non-agriculture market access (NAMA) is result of unreachable concession because of cost that will be received by developed and developing countries based on issue-linkages between agriculture, services, and non-agriculture market access (NAMA). Therefore this article will explain correlation between issue-linkages and unreachable agreement in agriculture, services, and non-agriculture market access (NAMA).Keywords: Doha Round, agreement, negotiation, non-agriculture market access (NAMA), cost, benefit, issue-linkages.DOI:https://doi.org/10.33005/jgp.v2i01.1980